The Comparison of Guanxi and Relationship Marketing on Business Management- A Case Study of Traditional and New Industries in Taiwan - HSU, WEI-LUN (2007)
Guanxi and Relationship Marketing (RM) are fundamentally different and they act as major marketing paradigms that have been adopted through different industries presently. Several scholars have various opinions about the future developments of guanxi and RM. This study, thus, firstly aims to comprehensively compare guanxi and RM from four perspectives; they are personal factors, companionship networks, leadership skills and society and culture. This paper views Taiwanese industries as a case study to further analyze the applications and future tendencies of guanxi and RM based on above four perspectives. This study then employs both quantitative and qualitative methods for further research. The AHP serves as quantitative method while the in-depth interview serves as qualitative method. The findings of the AHP suggest that the Taiwanese traditional industries largely tend to apply guanxi whereas the Taiwanese new industries largely tend to apply RM. The findings of the in-depth interview further suggest that guanxi is more significant in the criteria of companionship networks while RM is more significant in the criteria of working environment. Furthermore, this paper concludes that guanxi and RM might gradually develop into integration.